Improving the reporting of randomised trials: The CONSORT Statement andbeyond - Altman, D; Moher, D; Schulz, K (2012)
An extensive and growing number of reviews of the published literature demonstrate that health research publications have frequent deficiencies. Of particular concern are poor reports of randomised trials, which make it difficult or impossible for readers to assess how the research was conducted, to evaluate the reliability of the findings, or to place them in the context of existing research evidence. As a result, published reports of trials often cannot be used by clinicians to inform patient care or to inform public health policy, and the data cannot be included in systematic reviews. Reporting guidelines are designed to identify the key information that researchers should include in a report of their research. We describe the history of reporting guidelines for randomised trials culminating in the CONSORT Statement in 1996. We detail the subsequent development and extension of CONSORT and consider related initiatives aimed at improving the reliability of the medical research literature. © 2012 John Wiley and Sons, Ltd.